Body composition and anaerobic power: correlational analysis in male athletes - Ali, H.; Omoush, R.; Amawi, A.; Ghazzawi, H. (Frontiers in Sports and Active Living, 2025)
Background: Body composition monitoring is vital to improve functional performance outcomes such as power output and fatigue resistance in athletes.